The Long and the Short of it: Gene and Environment Interactions During Early Cortical Development and Consequences for Long-Term Neurological Disease - Stolp, Helen; Neuhaus, Ain; Sundramoorthi, Rohan; Molnar, Zoltan (Frontiers in Psychiatry, 2012)
Cortical development is a complex amalgamation of proliferation, migration, differentiation and circuit formation. These processes follow defined timescales and are controlled by a combination of intrinsic and extrinsic factors. It is currently unclear how robust and flexible these processes are and whether the developing brain has the capacity to recover from disruptions to normal cortical development. What is clear is that there are a number of cognitive disorders or conditions that are elicited as a result of disrupted cortical development, although it may take a long time for the full pathophysiology of the conditions to be realised clinically. The critical window for the manifestation of a neurodevelopmental disorder is prolonged, and there is the potential for a complex interplay between genes and environment. While there have been extended investigations into the genetic basis of a number of neurological disorders, limited definitive associations have been discovered. Many environmental factors, including inflammation and stress, have been linked to neurodevelopmental disorders, and it may be that a better understanding of the interplay between genes and environment will speed progress in this field. In particular, the development of the brain needs to be considered in the context of the whole materno-foetal unit as the degree of the metabolic, endocrine or inflammatory responses, for example, will greatly influence the environment in which the brain develops. This review will emphasize the importance of extending neurodevelopmental studies to the contribution of the placenta, vasculature, cerebrospinal fluid, and to maternal and foetal immune response. These combined investigations are more likely to reveal genetic and environmental factors that influence the different stages of neuronal development and potentially lead to the better understanding of the aetiology of neurological disorders such as autism, epilepsy, cerebral palsy and schizophrenia.